Penerapan Prinsip Good Governance dalam Kebijakan Pengelolaan Sampah di Kabupaten Banyumas: Studi Kasus Era Achmad Husein - Rosyidah, Hanik (Manabia: Journal of Constitutional Law, 2024)
The waste problem is a complex environmental problem. In reality, not many leaders are able to commit to solving the waste problem. The waste crisis in Banyumas Regency which peaked in 2018, also made Achmad Husein, as Regent of Banyumas at that time, directly involved in handling the problem, even using his personal funds. This research analyzes Achmad Husein's leadership character, which has good governance principles, as well as the economic impact of the waste management initiated by him. The research was carried out using a qualitative approach with data collection techniques in the form of content analysis, using the content of kasisolusi’s podcast. Research findings show that Achmad Husein's leadership character reflects the principles of good governance in the form of participation, transparency, accountability, effectiveness and efficiency, responsiveness and equity. Achmad Husein's use of personal funds indicates his commitment and integrity in solving urgent problems. This dedication has produced results that have had a significant economic impact on the welfare of society. Apart from that, the success of the SUMPAH BERUANG (Enchant Trash Turns Money) program, has made Banyumas becoming a representative for Smart Green ASEAN Cities. The excellent solution to the waste problem in Banyumas has become a sustainable waste management system. It is hoped that the results of this research provides motivation for all communities to recommit in taking responsibility for mandated work and distance themselves from corrupt behavior in overcoming various problems, especially threatening environmental problems.